Karakteristik Fisik Gelatin dari Kulit Ikan Nila (Oreochromis niloticus) Hasil Ekstraksi Menggunakan Asam Organik: The Physical Characteristics of Nile Tilapia (Oreochromis niloticus) Fish Skin Gelatin Extracted Organic Acids - Kartika Gemma Pravitri; Ni Wayan Putu Meikapasa; Destiana Adinda Putri (Jurnal Teknologi dan Mutu Pangan, 2026)
Tilapia skin contains high levels of collagen, making it a suitable raw material for gelatin production. To convert collagen into gelatin, pretreatment is required by soaking the skin in an acid solution. The objective of this study was to determine the physical characteristics of gelatin from tilapia skin using organic acids (lactic acid and acetic acid) and different extraction temperatures (60°C and 70°C). This study used a completely randomized factorial design with treatments using acetic acid at an extraction temperature of 60°C, acetic acid at an extraction temperature of 70°C, lactic acid at an extraction temperature of 60°C, and lactic acid at an extraction temperature of 70°C. The results showed that the best results were obtained from the treatment of lactic acid with an extraction temperature of 70°C, with a yield of 15.69% and a viscosity of 4.1 cPs. Meanwhile, the gel strength ranged from 4.17 to 4.34 gBloom, which means that this tilapia gelatin cannot yet form a gel. As for the color parameter, the highest brightness level was obtained in the lactic acid treatment with an extraction temperature of 60°C. This study concludes that the use of acetic acid and lactic acid, as well as different extraction temperatures, can increase the yield, viscosity, and color intensity of gelatin. Therefore, this study is expected to serve as the basis for the development of a more efficient and environmentally friendly extraction method.